2021
DOI: 10.21315/aamj2021.26.2.5
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Roles of GDP on the Relationship Between Income Inequality and Life Expectancy

Abstract: This study examined the mediation effect of gross domestic product (GDP) on the relationship between life expectancy and income inequality based on data from 23 Organisation for Economic Co-operation and Development (OECD) countries for 2004 through 2014. To form a theoretical framework, Preston curve and Kuznets curve were employed. The study set up a mediation model with life expectancy as an outcome variable, GDP as a mediator variable, and three variables characterising income inequality as predictor varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…In general, the results demonstrated that economic indicators themselves were weaker predictors of the natural movement of the population; however, at the same time, GDP clearly mediates the effect of predictor variables on life expectancy and other demographic indicators, although the extent of the impact varies [14,26].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In general, the results demonstrated that economic indicators themselves were weaker predictors of the natural movement of the population; however, at the same time, GDP clearly mediates the effect of predictor variables on life expectancy and other demographic indicators, although the extent of the impact varies [14,26].…”
Section: Discussionmentioning
confidence: 86%
“…Meanwhile, healthcare system efficiency plays an important role in enhancing life expectancy; several studies even suggest a correlation between higher GDPs per capita and increased life expectancy [11][12][13][14]. This relationship suggests that wealthier nations tend to have better healthcare outcomes, likely due to more resources being invested into health infrastructure, technologies, and services.…”
Section: Introductionmentioning
confidence: 99%
“…There are many cross-country papers that focus on the relationship between income inequality and average health status. For example, the negative effect of income inequality on average health status is shown to be larger in countries characterised by market-based more than community-based health-care strategies [ 67 ], a larger range of age and gender inequality [ 68 , 69 ], a larger range of relative poverty [ 70 ], a larger range of absolute poverty [ 71 ] or a less efficient health-care system [ 72 ].…”
Section: Discussionmentioning
confidence: 99%